Development and Psychometric Properties for Scale of Marital Intimacy in Couples - Shafiq, Sameera; Naz, Iram (Pakistan Journal of Humanities and Social Sciences, 2023)
The aims of the present study are the development and evaluation of the psychometric properties of Scale of Marital Intimacy (SMI) in married couples. The study methodology has used cross sectional research design and couples were selected with the purposive sampling technique. The development of the scale was based on deductive approach. Sixty items were selected after expert evaluation. In try-out phase, 50 couples were selected by purposive sampling technique. The items were found to be comprehendible by the couples and 54 items showed acceptable ? 0.30 item total correlation coefficient and 0.96 Cronbach’s Alpha reliability coefficient. In pilot study, 150 couples were selected by purposive sampling technique and exploratory factor analysis (EFA) was conducted. A total of 52 items were retained after EFA. These items were administered on another sample of 125 couples selected by purposive sampling technique. Confirmatory factor analysis (CFA) yielded 16 items for SMI and five subscales. The results in try-out of 54 items showed item-total correlation coefficient from 0.303 to 0.812 in acceptable range. EFA on 54 items yielded acceptable Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO) and Bartlett's Test of Sphericity with factor loading ?0.40 of 52 items. CFA showed model fit p<0.001 that established the structure validity and significant loading of the items in its subscales after eliminating 36 items. Final version of Scale of Marital Intimacy retained 16 items with acceptable Cronbach’s Alpha reliability coefficient. Conclusively, SMI is a reliable indigenous scale for measuring levels of marital closeness in couples with five sub-scales in Pakistan.